Poly(vinyl alcohol) nanocomposites containing reduced graphene oxide coated with tannic acid for humidity sensor - Lim, Min-Young; Shin, Huiseob; Shin, Dong Myung; Lee, Sang-Soo; Lee, Jong-Chan (ELSEVIER SCI LTD, 2016)
Poly(vinyl alcohol) (PVA) nanocomposites were prepared by a solution casting method using a reduced graphene oxide coated with tannic acid (rGO-TA) as a filler. The rGO-TA was simply prepared by mixing tannic acid (TA) with graphene oxide (GO). The simple mixing process was found to be effective to reduce GO and to produce covalently-grafted TA layers on the reduced GO. The mechanical properties of PVA were much improved by the addition of rGO-TA because the TA layers increased the compatibility of the reduced GO with PVA matrix. For example, Young's modulus and elongation at break values of PVA were increased by 34.0 and 56.9%, respectively, by adding 1.0 wt% of rGO-TA. In addition, the PVA nanocomposites showed excellent humidity sensing properties over the wide relative humidity range and the long-term stability due to the conductive property of the reduced GO and the enhanced mechanical strength by the effective incorporation of rGO-TA into the PVA matrix. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: MECHANICAL-PROPERTIES; POLYMER NANOCOMPOSITES; FACILE PREPARATION; CARBON NANOTUBES; COMPOSITES; MEMBRANES; STRENGTH; FUNCTIONALIZATION; POLYETHYLENE; TEMPERATURE